Medical Technologies Evaluation Programme: A review of NICE progression decisions, 2010–2013. Issue 3 (September 2016) - Keltie, Kim; Bousfield, Derek R; Cole, Helen; Sims, Andrew J
Abstract: Objectives: To review the progression decisions for notifications considered at National Institute of Health and Care Excellence (NICE) Medical Technology Advisory Committee (MTAC) meetings during its first three years (2010–2013) to identify trends. Methods: The list of medical devices discussed at committee, briefing notes, committee decisions, and non-progression letters, where applicable, were obtained from NICE. Each medical device presented to committee was classified using five different medical device categorisation systems. Trends in progression decision, scores against programme selection criteria over time, and reasons provided by committee to support the non-progression decision, were analysed. Results: Between January 2010 and March 2013 31 MTAC meetings were held. Of the 110 medical technologies considered, 45 were given a progression decision (23 selected for Medical Technologies Guidance development, 22 routed for guidance development in other NICE programmes), 64 did not progress to guidance development and 1 was excluded from analysis whilst awaiting final committee decision. The six programme categories and total scores were not sensitive or specific predictors of progression to guidance decision. No significant change in the proportion selected for progression over time was observed ( P >0.05). No compelling evidence of an association between the type of medical device and progression decision was found. Fifteen distinct reasons for non-progression were identified; 'lack of evidence' being provided in the majority, 93.8%, of cases. Conclusions: During its first three years, MTAC׳s progression decisions for guidance development on medical technologies were not associated with device type and there is no evidence of changes over time. Highlights: Review of Medical Technology Advisory Committee (MTAC) progression decisions during first 3 years of establishment. No trend in the proportion of medical devices progressing to guidance development was observed over time. Progression to NICE guidance development was not associated with medical device type.